Przestrzeń i jej kulturowe reprezentacje: Od Redakcji - Izdebska, Agnieszka; Konończuk, Elżbieta (Zagadnienia Rodzajów Literackich, 2023)
The text concerns the consequences of the appearance in the humanities of a phenomenon called the “spatial turn”, which is one of the aspects of the cultural turn. It is a subject of unwavering interest amongst researchers and is broadly understood as an experience of space inhabited and traversed, close and distant, familiar and foreign, open and closed, real and imagined, visually and remembered. Problems related to recording such an experience and its interpretation have prompted those practicing such reflection to look for new methodologies within interdisciplinary studies developed at the intersection of literary studies, cultural studies, geography, history and sociology. The consequence of such attempts is the emergence of new subdisciplines within various humanities. Such as, for example: geopoetics, geoaesthetics, humanistic and cultural geography, autogeobiography and topocentric history. The article also draws attention to the relationship between scientific research in this field and creative practice, mainly literary practice. A large part of the text is devoted to a review of the texts included in this issue of “The Problems of Literary Genres”/”Zagadnienia Rodzajów Literackich” and how they fit into the theoretical reflection under the sign of the spatial turn. The thematic scope here is wide and is not limited only to analyses of literary works. Several articles have been devoted to, for example, spatial film contexts